The antecedents of loyalty patronage behaviour - Osman M. Zain; Muayyad Jabri (Penerbit Universiti Kebangsaan Malaysia, 1996)
This, study tests the model of loyalty patronage behaviour which involves lifestyles, shopping orientations, past purchase experiences, and alternately customers store image and store image congruity. The results of this study supported the proposed model, while suggesting the inclusion of the influence of lifestyles on past purchase experiences. It also concludes that it is sufficient for future research on loyalty palronage to use either customers store image or store image congruity.